Effects of rare earth as feed additive on production performance, egg quality, serum biochemical parameters, antioxidant capacity, intestinal morphology, and gut microbiota in late-phase laying hens - Li, Jiaming; Yan, Liwen; Cao, Xuehai; Luo, Yueming; Peng, Xintong; Wang, Zirui; Zou, Tiande; Chen, Jun; You, Jinming (Frontiers in Sustainable Food Systems, 2023)
This study aimed to investigate the effects of dietary rare earth (RE) supplementation on production performance, egg quality, serum biochemical parameters, antioxidant capacity, intestinal morphology, and gut microbiota in late-phase laying hens. A total of 960 Lohmann Pink laying hens (380 d old) were randomly assigned to 1 of 5 dietary treatments in a 21-day feeding trial. There were 6 replicates in each treatment, with 32 hens per replicate. The five experimental diets were supplemented with 0, 150, 300, 450, and 600 g/t RE in the basal diet. Compared with the control group, hens fed the 150 g/t RE diet had a greater average egg weight during the third week of the experimental period (p < 0.05). However, dietary 150, 300, or 600 g/t RE supplementation decreased the eggshell thickness of laying hens compared to that of the control group (p < 0.05). No differences were observed in the serum biochemical parameters of laying hens among treatments except for the HDL-C concentration, which was higher in the 300 or 450 g/t RE-supplemented group than in the control group (p < 0.05). However, GSH-Px activity increased when hens were fed the 600 vs. 0 g/t RE diet (p < 0.05). But dietary supplementation with 600 g/t RE increased the ileum’s crypt depth in laying hens compared to the control group (p < 0.05). There were significant differences in beta diversity of cecum microbiota in laying hens fed a 600 g/t RE diet in place of the other 4 experimental diets (p < 0.05). Compared with the control diet, dietary 600 g/t RE supplementation significantly decreased the relative abundance of Fusobacteriota (phylum) and Fusobacterium (genus) while markedly increasing the relative abundance of Ruminococcus (genus) and Subdoligranulum (genus) (p < 0.05). A high RE dosage negatively affects egg quality and intestinal morphology and alters gut microbiota diversity and composition. In contrast, a moderate RE dosage has beneficial effects on production performance in late-phase laying hens. Further research is warranted regarding eggshell thickness to investigate whether dietary calcium levels must be adjusted when 150 g/t RE is supplemented for late-phase laying hens.